2010
DOI: 10.1155/2010/701657
|View full text |Cite
|
Sign up to set email alerts
|

Immune Suppression in Head and Neck Cancers: A Review

Abstract: Head and neck squamous cell carcinomas (HNSCCs) are the sixth most common cancer in the world. Despite significant advances in the treatment modalities involving surgery, radiotherapy, and concomitant chemoradiotherapy, the 5-year survival rate remained below 50% for the past 30 years. The worse prognosis of these cancers must certainly be link to the fact that HNSCCs strongly influence the host immune system. We present a critical review of our understanding of the HNSCC escape to the antitumor immune respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
142
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(151 citation statements)
references
References 170 publications
(144 reference statements)
2
142
0
7
Order By: Relevance
“…14 In addition, decreased expression of NKG2D receptors has also been shown to impair NK cell function in HNSCC patients. 15,16 Indeed, similar effects have been demonstrated in regards to other malignancies, such as colorectal cancer, prostate cancer, neuroblastoma, and several types of leukemia. 11,[17][18][19] Interestingly, we demonstrated that sMICA and transforming growth factor b 1 (TGFb 1 ) compromise the function of activated donor NK cells applied as an immunotherapeutic approach in children with neuroblastoma after haploidentical stem cell transplantation (HSCT).…”
Section: Introductionmentioning
confidence: 59%
“…14 In addition, decreased expression of NKG2D receptors has also been shown to impair NK cell function in HNSCC patients. 15,16 Indeed, similar effects have been demonstrated in regards to other malignancies, such as colorectal cancer, prostate cancer, neuroblastoma, and several types of leukemia. 11,[17][18][19] Interestingly, we demonstrated that sMICA and transforming growth factor b 1 (TGFb 1 ) compromise the function of activated donor NK cells applied as an immunotherapeutic approach in children with neuroblastoma after haploidentical stem cell transplantation (HSCT).…”
Section: Introductionmentioning
confidence: 59%
“…23 The incidence of SCC has been increasing faster and faster. 24 In the US, there were 53,640 new cases and 11,520 deaths due to SCC of the head and neck in 2013.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 In this process, neoplastic cells recruit different cell types that are able to suppress the immune response in the tumor microenvironment, particularly regulatory T (Treg) cells. 5 Treg cells are derived from the lymphocyte lineage that constitutively expresses CD4, CD25, and the nuclear transcription factor -forkhead box P3 (FoxP3).…”
Section: Introductionmentioning
confidence: 99%